2011
DOI: 10.1016/j.vaccine.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with PCEP microparticles containing pertussis toxoid, CpG ODN and a synthetic innate defense regulator peptide induces protective immunity against pertussis

Abstract: We investigated the efficacy of a novel microparticle (MP) based vaccine formulation consisting of pertussis toxoid (PTd), polyphosphazene (PCEP), CpG ODN 10101 and synthetic cationic innate defense regulator peptide 1002 (IDR) against Bordetella pertussis in mice. We studied whether encapsulation of these IDR-CpG ODN complexes into polyphosphazene-based microparticles further enhanced their immunomodulatory activity compared to soluble formulations containing PCEP (SOL), or without PCEP (AQ). In vitro stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 26 publications
1
40
0
2
Order By: Relevance
“…Anti-infective peptides IDR-1 and IDR-1002 confer in vivo protection against bacterial infections through modulation of innate immune responses, including the regulation of chemokine/cytokine responses and recruitment of monocytes to the site of infection [3,4]. Likewise, IDR-1018 and IDR-HH2 also demonstrate the ability to modulate the host cytokine/chemokine environment [26,27], while both IDR-1002 and IDR-HH2 promote adjuvant activity in formulation [5,6]. We sought to determine whether the ability to promote monocyte adhesion to fibronectin demonstrated by IDR-1002 was shared with other IDR peptides as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-infective peptides IDR-1 and IDR-1002 confer in vivo protection against bacterial infections through modulation of innate immune responses, including the regulation of chemokine/cytokine responses and recruitment of monocytes to the site of infection [3,4]. Likewise, IDR-1018 and IDR-HH2 also demonstrate the ability to modulate the host cytokine/chemokine environment [26,27], while both IDR-1002 and IDR-HH2 promote adjuvant activity in formulation [5,6]. We sought to determine whether the ability to promote monocyte adhesion to fibronectin demonstrated by IDR-1002 was shared with other IDR peptides as well.…”
Section: Resultsmentioning
confidence: 99%
“…While a common feature of IDR peptides is their ability to enhance cellular infiltration to sites of infection, mechanistic studies to date have focused on the indirect stimulation of chemotaxis, through the stimulation of chemokine production, rather than any direct effects on cellular motility. In this study, we identified a mechanism by which synthetic peptide IDR-1002 directly enhances monocyte migration, a hallmark effect in IDR-mediated protection against bacterial infection [3,4] and its deployment in adjuvant formulations [5,6]. Specifically, we demonstrated that IDR-1002 enhanced monocyte migration towards chemokines through a fibronectin matrix by strengthening the interaction between monocytes and this substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, HDP-based peptides have been shown to enhance vaccination efficiency in several in vivo models, in which the vaccination mixture contains synthetic DNA (43)(44)(45)(46)(47). Although little is known about the effects of these specific HDPs on DNA-induced immune activation, it is possible that part of their efficacy comes from increasing the proinflammatory DNA-induced immune response.…”
Section: Discussionmentioning
confidence: 99%
“…4,21 The primary aim of pertussis immunisation is to protect young infants against severe Despite the well-established pertussis immunisation programs in Australia and overseas, infants younger than six months of age continue to be at highest risk of severe outcomes. 10,86,89,[103][104][105][106] In the future, new pertussis vaccines may be able to provide earlier and longer lasting protection by utilising live attenuated B. pertussis strains, novel soluble or micro-particle vaccine formulations, improved adjuvants, or mucosal delivery, [107][108][109] however as these novel vaccines may still be many years away, other strategies need to be considered to protect young infants. 10,61,103,105 The "cocoon" strategy, which attempts to protect newborn infants by immunising their close contacts, such as parents and other caregivers, has been proposed as a possible solution.…”
Section: Immunisation Strategies and Coveragementioning
confidence: 99%